THE EFFECTIVENESS OF COORDINATION EXERCISES IN DEVELOPING TECHNICAL SKILLS IN ADOLESCENT FOOTBALL PLAYERS (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
This article is dedicated to the scientific analysis of the effectiveness of coordination exercises in developing technical skills in adolescent football players. The adolescent period (10-16 years) is a critical stage for developing technical skills due to the active development of the neuromuscular system and motor abilities. The article examines the impact of coordination exercises focused on balance, proprioception, agility, and reaction speed on technical skills such as dribbling, passing, shooting, and ball control. Research indicates that regular training programs lasting 8-12 weeks can improve technical skills by 20-35%, while also reducing injury risks and enhancing overall athletic potential. The article discusses experimental research results, statistical analyses, and the practical benefits of integrating coordination exercises into football training programs. The need to explore gender differences, long-term effects, and individualized approaches in future research is emphasized.